Effect of treatment on erythrocyte phosphoribosyl pyrophosphate synthetase and glutathione reductase activity in patients with primary gout. Issue 11 (November 1986) - Braven, J; Hardwell, T R; Hickling, P; Whittaker, M
Abstract : The activities of erythrocyte phosphoribosyl pyrophosphate (PRPP) synthetase and glutathione reductase (GTR) were studied in 26 patients with primary gout who were receiving no treatment or treatment with either allopurinol or azapropazone, and compared with the activity in a group of healthy controls. The activity of PRPP synthetase was significantly higher in the gout group and was not influenced by either drug. No significant difference in the activity of GTR was observed. The failure of either drug to suppress the increased activity of PRPP synthetase associated with gout is discussed.